From Open Cast to Block Cave and the Effects on the Autogenous Milling Circuit at Palabora Mining Copper - P. Condori (Canadian Institute of Mining, Metallurgy and Petroleum, 2012)
Palabora Mining Copper (PMC) has two autogenous mills that have been in operation since 1976. The mills were originally designed to treat 30 000 t/d of open cast copper ore in a closed circuit with cyclones. As the ore body went deeper the open cast method of mining was changed to block caving, a consequence of this was the dolerite content (hardest barren material) increased significantly, increasing the production rate of pebbles and thus reducing the milling capacity. In order to cope with the increased ore hardness and to increase mill capacity, a second ball milling stage and pebble crushing were incorporated to the circuit. The above actions created new challenges to the circuit operation and bottlenecks in different areas of the milling circuit. This paper reports the holistic work performed on the Palabora autogenous milling circuit including the implementation of a mill constraint control scheme, the implementation of a pebble removal system from the circuit and a new circuit configuration. The achieved plant stability and increment of ore throughput are also reported in this paper.